ANALYSIS OF THE PROCESS OF FORMATION OF THE ECONOMIC COMPETENCE OF FUTURE SPECIALISTS OF THE CHEMICAL INDUSTRY - Хохлова , Олександра (Socio-economic relations in the digital society, 2019)
The article analyzes the process of formation of the economic competence of future specialists of the chemical industry in the educational process of higher educational institutions of Ukraine. The article assesses the impact of economic competence, which is based on the results of the analysis of economic disciplines provided by training programs in the areas of “Chemical technology” and “Engineering”, as well as on the analysis of the structure of the section “Economic calculation” of the graduation project. The deficiencies in the maintenance of the economic part of the program of training of future specialists in the chemical industry, which can lead to erroneous conclusions of students on the prioritization of those or other economic problems are identifi ed and described. The direction of further research is determined to explore the possibilities of making changes and additions in the economic part of education and training programs to bring its content in accordance with the actual requirements of modernity.